SISTEM KOMPUTERISASI PEMELIHARAAN MESIN PRODUKSI PADA PT. KUBOTA INDONESIA (Information Technology and Telematics, 2015)
Abstract - The aim of the thesis was to design and implement a computerized system on a production engine maintenance company. The method used in this research is the method of analysis and design method in which the method of analysis , the authors analyze the needs and through this analysis the authors designed the stage - the stage to be carried out . The result achieved is to support the implementation of maintenance activities at the company , such as data processing machines , components , manufacture of scheduling , and the provision of required reports . Conclusions with the new system delays the flow of information can be prevented because data processing and report generation has been done in computerized so that it can accelerate better maintenance . Keywords : Computerized , maintenance .